Implementation of the CTL Learning Model in PAI Subjects at Wyata Dharma Middle School, Bandung - Lilis Fauziah Balgis; Muhammad Kafnun Kafi; Didin Syamsudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to create learning that is fun and easy to understand using varied learning models. It is hoped that this will reduce saturation and increase students' learning motivation, so that the teaching and learning process becomes more effective. This research is class action research conducted at Wyata Dharma Middle School Bandung, where teachers teach directly using students' worksheets (LKPD). This research is casuistic, focusing on conditions and situations in the classroom, with the aim of solving problems to improve the quality of learning. This research discusses the use of the Contextual Teaching and Learning (CTL) learning model, its implementation steps, and its implementation in class IX A. Observations show that students are enthusiastic in discussions and working on LKPD questions, assisted by PowerPoint and LKPD learning media which makes it easier for them to understand the material.